Investigations of LPS endotoxin elimination in the flowing column conditions with the sorbent on the basis of carbonized rice husk (Experimental biology, 2015)
This research work is devoted to study lipopolysaccharide (LPS) detoxication on the basis of its sorption by nanostructured carbonized rice husk from biological liquids.During experimental tests it is established that in the flowing column conditions with carbonized rice husk the elimination of LPS endotoxin from biological liquids shows 98%.
Keywords: phytoextract; carbonized rice husk; sorbent; antimicrobial properties; functionalizathion; herbal plants; toxic infections; purulent inflammation processes